4p16.1-p15.31 duplication and 4p terminal deletion in a 3-years old Chinese girl: Array-CGH, genotype-phenotype and neurological characterization. (July 2015) - Piccione, Maria; Salzano, Emanuela; Vecchio, Davide; Ferrara, Dante; Malacarne, Michela; Pierluigi, Mauro; Ferrara, Ines; Corsello, Giovanni
Abstract Background Microscopically chromosome rearrangements of the short arm of chromosome 4 include the two known clinical entities: partial trisomy 4p and deletions of the Wolf-Hirschhorn critical regions 1 and 2 (WHSCR-1 and WHSCR-2, respectively), which cause cranio-facial anomalies, congenital malformations and developmental delay/intellectual disability. Methods/results We report on clinical findings detected in a Chinese patient with a de novo 4p16.1-p15.32 duplication in association with a subtle 4p terminal deletion of 6 Mb in size. This unusual chromosome imbalance resulted in WHS classical phenotype, while clinical manifestations of 4p trisomy were practically absent. Conclusion This observation suggests the hypothesis that haploinsufficiency of sensitive dosage genes with regulatory function placed in WHS critical region, is more pathogenic than concomitant 4p duplicated segment. Additionally clinical findings in our patient confirm a variable penetrance of major malformations and neurological features in Chinese children despite of WHS critical region's deletion.